English language teachers’ conceptualizations of one-to-one private tutoring: An international phenomenographic study - WERBIŃSKA, DOROTA; BOZYIǦIT, ELIF; GUERRA, LUÌS; EKIERT, MAŁGORZATA; KӦSE, SERHAN (Glottodidactica, 2019)
Private English tutoring, understood as the paid English teaching service offered to students to supplement their learning of English at school or prepare them for an examination in English, has become a popular out-of-school learning activity. In order to obtain deeper insights into its intricacies, the need arises to examine the experience of one of its pivotal stakeholders – the private tutors. This article is based on a phenomenographic study with a view to investigating the conceptions of private tutoring held by 15 English teachers from three countries (Poland, Portugal, and Turkey) who offer private teaching services in English in their local contexts. The findings suggest that there are at least three conceptions according to which private tutoring can be experienced by the participants: as a source of income, as helping, and as professional development. The study also poses the question if there is space for formal training of private tutors and calls for further research into English private tutoring.